Feasibility Study of Pulp Mill Integrated Hydrogen Production from Gasified Black Liquor – - Pednekar, Ketan (My University, 2003)
Due to expected increased future demand of CO2 neutral fuels and improvement in fuel cell technology, it is interesting to explore the possibilities of producing hydrogen from biomass resources. Black liquor is an important bio-fuel source. The feasibility of integrated hydrogen production from gasified black liquor available from a reference pulp mill was studied in this project. The reference pulp mill used was the Eco-cyclic pulp mill (KAM), a model mill developed in a Swedish national research programme using existing best available technologies. Various process options were explored and a representative model was developed based on existing proven technologies for hydrogen production. The model was developed using a general-purpose simulation software ‘Hysys’. The results show that it would be possible to produce 66.5 ktonnes of hydrogen per year from the black liquor solids available from the reference pulp mill (corresponding pulp production 2000 ADt (air dried tonnes) per day). The steam and power production were compared with the pulp mill demand. The associated bark and power imports to cover the deficit of steam and power were calculated. The study shows that to satisfy the pulp mill steam demand around 200% of dry bark produced in the reference pulp mill must be imported. All the pulp mill power demand in addition to the power demand of the proposed production unit (approximately 50% of the pulp mill demand) must be purchased from the grid if all the hydrogen produced is to be exported. A comparative study of steam and power production from other black liquor energy and chemical recovery systems such as conventional recovery boiler, Black liquor gasification with combined cycle (BLGCC) and methanol production process was performed. It was observed that with in-house power production through fuel cells, the power production of a hydrogen production unit is comparable to the recovery boiler, but much less than the BLGCC. The produced hydrogen, if used in fuel cell powered vehicles, has a potential of replacing 0.36 million tonnes of gasoline. The corresponding potential for replacement of gasoline via the methanol production route is 0.2 million tonnes. The CO2 capture possibilities were also explored in the process.
Keywords: Kemiteknik; Chemical Engineering